2022
DOI: 10.3389/fped.2022.977827
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory abnormalities after infection with SARS-CoV-2 – A prospective case-control study in children and adolescents

Abstract: BackgroundLong-term neurological complaints after SARS-CoV-2 infection occur in 4–66% of children and adolescents. Controlled studies on the integrity of the peripheral nerve system are scarce. Therefore, we examined the somatosensory function in children and adolescents after SARS-CoV-2 infection in a case-control study compared with age-matched individuals.Materials and MethodsEighty-one subjects after SARS-CoV-2 infection (n = 44 female, 11.4 ± 3.5 years, n = 75 SARS-CoV-2 seropositive, n = 6 PCR positive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…The prevalence of neuropathic pain in patients with COVID-19 infection reported in the literature varies between 0.4% and 25% [14,29,30,35,36], whereas the prevalence of paresthesia varies between 6% and 33% [15,37]. Miller et al [36] detected peripheral nerve injury in the upper extremity in 15 of the 114 COVID-19 patients hospitalized in the prone position and treated in the intensive care unit for an average of 32.5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of neuropathic pain in patients with COVID-19 infection reported in the literature varies between 0.4% and 25% [14,29,30,35,36], whereas the prevalence of paresthesia varies between 6% and 33% [15,37]. Miller et al [36] detected peripheral nerve injury in the upper extremity in 15 of the 114 COVID-19 patients hospitalized in the prone position and treated in the intensive care unit for an average of 32.5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sensory symptoms attributed to the PACS seem unrelated to the gravity of the previous infection (7). Interestingly, a recent case-control study on children and adolescents with previous SARS-CoV2 infection reported increased thermal and vibration thresholds; the mechanical detection threshold with SWMT did not differ from the control group, but there was a significant difference within the SARS-CoV2 group when the patients with previous symptomatic infection and those with asymptomatic infection were compared (10). These studies highlight the involvement of small-diameter sensory fibers (C-fibers and A-delta fibers) due to SARS-CoV2 infection; moreover, the involvement of large sensory fibers was evident only when they compared the patients with previous symptomatic SARS-CoV2 infection to those who had The SPG was in the normality range in every subject.…”
Section: Introductionmentioning
confidence: 90%
“…A. Neurological symptoms Fatigue (tiredness) 0.7-71.1 Borch 42), † , Stephenson 35), † , Sterky 41) , Ashkenazi-Hoffnung 18) , Brackel 19) , Say 8) , Roge 39) , Buonsenso 9) , Molteni 25) , Osmanov 27) , Radtke 22) , Katsuta 32) , Eitner 73) , Petersen 75) Headache 6.9-80 Brackel 19) , Molteni 25) , Smane 26) , Borch 42), † , Stephenson 35), † , Roge 39) , Kikkenborg 15), † , Ashkenazi-Hoffnung 18) Confusion 5.6-6.5 Zavala 43), † , Stephenson 35), † Dizziness 3-8.9 Borch 42), † , Stephenson 35), † , Brackel 19) , Kikkenborg 15), † , Ashkenazi-Hoffnung 18) Memory loss 13-17.8 Brackel 19) , Ashkenazi-Hoffnung 18) Brain fog 2 Brackel 19) B. Neurosensory symptoms Anosmia (loss of smell) 1.1-84 Borch 42), † , Stephenson 35), † , Sterky 41) , Molteni 25) , Smane 26) , Zavala 43), † , Katsuta 32) , Petersen 75) , Ashkenazi-Hoffnung 18) Ageusia (loss of taste) 1.0-16.7 Borch 42), † , Sterky 41) , Ashkenazi-Hoffnung 18) , Smane 26) , Katsuta 32) , Petersen 75) Eye pain 2.8-5.9…”
Section: Neuropsychiatric and General Conditionsunclassified